2021
DOI: 10.1371/journal.pone.0254890
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mobile phone text message reminder interventions to improve adherence to antiretroviral therapy among adolescents living with HIV: A systematic review and meta-analysis

Abstract: Background Poor adherence to antiretroviral therapy in adolescents living with HIV is a global challenge. One of the key strategies to improve adherence is believed to be the use of digital adherence tools. However, evidence is limited in this area. Our objective was to investigate the effectiveness of mobile phone text message reminders in improving ART adherence for adolescents. Methods The preferred reporting item for systematic review and meta-analysis guideline was followed. A literature search was done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
1
12
1
Order By: Relevance
“…One study [ 22 ] showed that compared to a control group, a group receiving text message–based support was more likely to maintain an adherence threshold at follow-up and meet the clinical goal of a higher CD4 cell count. However, another study [ 24 ], like ours, did not obtain this result. Our meta-analysis of the 4 studies that reported CD4 cell count showed considerable heterogeneity and no significant pooled mean difference.…”
Section: Discussioncontrasting
confidence: 67%
“…One study [ 22 ] showed that compared to a control group, a group receiving text message–based support was more likely to maintain an adherence threshold at follow-up and meet the clinical goal of a higher CD4 cell count. However, another study [ 24 ], like ours, did not obtain this result. Our meta-analysis of the 4 studies that reported CD4 cell count showed considerable heterogeneity and no significant pooled mean difference.…”
Section: Discussioncontrasting
confidence: 67%
“…Lived experiences of adolescents living with human immuno-deficiency virus … (Ndinohokwe Mukerenge) 813 adolescents ranging from stigma, poor adherence to treatment; lack of knowledge on HIV; challenges understanding ART treatment; poor disease management skills; challenges with disclosure, and psycho-social issues, among others [4]- [6]. Conversely, in SSA, adolescents living with HIV have suboptimal adherence to antiretroviral therapy (ART) with consequent lower viral load suppression rates and higher mortality risk than other populations [7]. The HIV care for adolescents living with HIV in this part of the world lacks effectiveness, as evidenced by increased mortality rates and poor health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, interest has grown in using digital adherence tools (DAT) with reminder cues through short message services (SMS) for improving adherence to treatment and retention in care. (22)(23)(24)(25)(26)(27) Several studies have found DATs with reminder SMS feasible among adult PLHIV. (28)(29)(30)(31) However, there is limited evidence of its effectiveness among CALHIV in improving adherence.…”
Section: Introductionmentioning
confidence: 99%